The Effect of Gamefied Instruction on Vocabulary and Motivation on Students at South Nias - kammer sipayung; Albertus Halawa (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Background: Gamified instruction is a challenging solution to problems in students’ vocabulary and motivation in rural areas like South Nias. This study aims to determine the effect of gamified instruction on students’ vocabulary ability and motivation. Methodology: The aims of this study were achieved by implementing a mixed research method (qualitative and quantitative). The experimental research design was used to determine the effect of treatment on vocabulary ability; however, a questionnaire and semi-structured interview were delivered to the experimental students. The sample of this study is 60 students. Findings: After analyzing the data, it is shown that the experimental group positively affects students’ motivation. The control group has a higher motivation but is not significant in their vocabulary achievement. In addition to that significant effect on experimental vocabulary achievement. Gamified instruction can be concluded as an efficient strategy to achieve learning goals. Conclusion: Gamified instruction can be an alternative solution for English teachers to improve student vocabulary and motivation to learn English as a foreign language. Originality: Most of the current studies focus on online media (platforms) and less research investigates vocabulary and students' motivation.